Jewish-Christian Dialogues on Scripture in Late Antiquity heretic narratives of the Babylonian Talmud - Bar Asher Sigal, Mikhal 1979- (New York Cambridge University Press, 2019)
Marshalling previously untapped Christian materials, Bar-Asher Siegal offers radically new insights into Talmudic stories about Scriptural debates with Christian heretics.
Cover -- Half-title -- Title page -- Copyright information -- Table of contents -- Acknowledgments -- 1 Minim Stories in the Talmud: Introductory Discussion -- Heretic Narratives of the Babylonian Talmud -- Minut As Heresy -- Minim and Christian Heresy -- Minim as Heretics in the Babylonian Talmud -- Heresy vs. "Heresiological Representations" -- Who are the Minim? -- Minim in the Babylonian Talmud -- A Rabbinic Literary Response to Contemporaneous Christian Views -- The Talmudic Minim as the Final Stage in the Altering Use of the Term -- Methodology -- Septuagint Version of the Verses -- Transmission of Christian Traditions into the Rabbinic Talmud -- Orality and Secondary Orality -- Constructing History from Texts -- 2 "A Fool You Call Me?": On Insult and Folly in Late Antiquity -- "Fool" in the New Testament -- Insults in the Ancient World -- "Fool" and doreshe .alaqot -- Doreshe ḥalaqot and req -- "It is Not an Empty Matter from you" in Rabbinic Literature -- "Our Full Torah" -- Matthew 5:22 and the Misinterpretation of the Law -- "Fool" in Rabbinic Literature -- Early Church Writers -- Conclusions -- 3 "He Who Forms the Mountains and Creates the Wind": Amos 4:13 and the Jewish-Christian Argument in B. Ḥullin 87A -- B. Sanhedrin 39a -- Amos 4:13 -- Amos 4:13 in Christian Writings -- The Christian Background for the Passage in b. Ḥullin -- Cyril of Alexandria, Basil of Caesarea and Ambrose of Milan -- Ḥullin 87a and the Christian Argument from Amos 4:13 -- Psalms 69:22 -- Good Tidings -- Three Days -- Standing at the Gate -- Falling off a Roof -- Do Not Gloat When Your Enemy Falls -- Fool -- Cup of Blessing -- Let Their Table be a Trap for Them -- Does the Second Min Subscribe to a Specific Theological View? -- Conclusions -- 4 "Rejoice, O Barren One Who Bore No Child": Isaiah 54:1 and the Jewish-Christian Argument in B. Berakhot 10A.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books